Effectiveness on level of consciousness of non-invasive neuromodulation therapy in patients with disorders of consciousness: a systematic review and meta-analysis - Liu, Zhenyu; Zhang, Xintong; Yu, Binbin; Wang, Jiayue; Lu, Xiao (Frontiers in Human Neuroscience, 2023)
Background: Disorders of consciousness (DoC) commonly occurs secondary to severe neurological injury. A considerable volume of research has explored the effectiveness of different non-invasive neuromodulation therapy (NINT) on awaking therapy, however, equivocal findings were reported. Objective: The aim of this study was to systematically investigate the effectiveness on level of consciousness of different NINT in patients with DoC and explore optimal stimulation parameters and characteristics of patients. Methods: PubMed, Embase, Web of Science, Scopus, and Cochrane central register of controlled trials were searched from their inception through November 2022. Randomized controlled trials, that investigated effectiveness on level of consciousness of NINT, were included. Mean difference (MD) with 95% confidence interval (CI) was evaluated as effect size. Risk of bias was assessed with revised Cochrane risk-of-bias tool. Results: A total of 15 randomized controlled trials with 345 patients were included. Meta-analysis was performed on 13 out of 15 reviewed trials indicating that transcranial Direct Current Stimulation (tDCS), Transcranial Magnetic Stimulation (TMS), and median nerve stimulation (MNS) all had a small but significant effect (MD 0.71 [95% CI 0.28, 1.13]; MD 1.51 [95% CI 0.87, 2.15]; MD 3.20 [95%CI: 1.45, 4.96]) on level of consciousness. Subgroup analyses revealed that patients with traumatic brain injury, higher initial level of consciousness (minimally conscious state), and shorter duration of prolonged DoC (subacute phase of DoC) reserved better awaking ability after tDCS. TMS also showed encouraging awaking effect when stimulation was applied on dorsolateral prefrontal cortex in patients with prolonged DoC. Conclusion: tDCS and TMS appear to be effective interventions for improving level of consciousness of patients with prolonged DoC. Subgroup analyses identified the key parameters required to enhance the effects of tDCS and TMS on level of consciousness. Aetiology of DoC, initial level of consciousness, and phase of DoC could act as significant characteristics of patients related to the effectiveness of tDCS. Stimulation site could act as significant stimulation parameter related to the effectiveness of TMS. There is insufficient evidence to support the use of MNS in clinical practice to improve level of consciousness in patients with coma.